Long-term testosterone replacement therapy reduces fatigue in men with hypogonadism - Maurício de Almeida Ferreira; José Alexandre Mendonça (BioExcel Publishing Ltd, 2022)
Background: Testosterone replacement therapy (TRT) is one of the main lines of treatment for men with hypogonadism. This study sought to evaluate the influence of TRT in men with late-onset hypogonadism (LOH), regarding fatigue, coronary artery disease (CAD), carotid intima-media thickness (CIMT) and cardiovascular risk. Methods: This study compared men with LOH already on TRT for >1 year to newly diagnosed men with LOH who recently started TRT (controls). We included men aged >18 years with clinical manifestations of testosterone deficiency and testosterone levels of <300 ng/dL documented in two separate occasions. Results: A total of 33 patients were included in the study group and 30 in the control group. Mean age was 49.1 years (±11.5) in those already under TRT for >1 year and 45 (±12.2) years in the control group (p=0.18). CAD was present in 14 (46.7%) patients in the control group and in 3 (9.1%) in the study group (p<0.001). TRT >1 year was not associated with lower rates of CAD in multivariable analysis. Fatigue Severity Score was significantly higher in the control group (39.2±15.0), compared to TRT >1 year (23.5±8.1; p<0.001). In a multivariable analysis adjusted for age and hypertension, TRT >1 year was associated with a 14.8-point decrease in Fatigue Severity Score (p<0.001). Overall, there were no differences between the study group and the control group regarding cardiovascular risk (p=0.31). Conclusion: TRT for >1 year was associated with significantly lower fatigue scores. No differences were observed regarding CIMT, CAD and cardiovascular risk according to the WHO-ISH scale.